COMPARISON OF DISTANCE BETWEEN MAXILLARY CENTRAL INCISORS AND INCISIVE PAILLA IN DENTATE INDIVIDUALS WITH DIFFERENT ARCH FORMS - Zia, Majid; Azad, Azad Ali; Ahmed, Salman (Journal of Ayub Medical College Abbottabad, 2009)
Background: After loss of natural teeth, provision of prosthodontic services almost becomes necessity in the present day living. To provide effective mastication teeth have peculiar forms. To make it more efficient both functionally and biologically, they are arranged in particular geometric manner referred to as dental arch. The objective of this study was to compare the distance between mesial edge of the maxillary central incisors and posterior border of the incisive papilla in dentate individuals with different arch forms. Methods: After sample selection, impressions were made for upper and lower arches and the resultant casts were standardised. Arch forms were assessed by their morphological description. Measurements on cast were recorded for incisive papilla (IP) and maxillary central incisor (CI) distance after securing it on cast surveyor. Results: Ovoid arch form was the most frequently observed arch form both in males (57%) and females (68%) while their combination (Ovoid Square and Ovoid tapered) were the least commonly observed arch forms (4% and 5% each). Gender seems to be important in about 1/4th of the dentate individuals, regarding both the type of the arches and CI-IP distance. Conclusion: Ovoid type of arches was the commonest arch form seen in either sex. There is no significant difference between males and females in ¾th of dentate individuals, regarding the type of dental arch as well as CI-IP distance. Keywords: Incisive papilla, arch forms, anatomic landmarks